2017
DOI: 10.1186/s13045-017-0397-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells as vehicles of tetravalent bispecific Tandab (CD3/CD19) for the treatment of B cell lymphoma combined with IDO pathway inhibitor d-1-methyl-tryptophan

Abstract: BackgroundAlthough blinatumomab, a bispecific T cell engaging antibody, exhibits high clinical response rates in patients with relapsed or refractory B-precursor acute lymphoblastic leukemia (B-ALL) and B cell non-Hodgkin’s lymphoma (B-NHL), it still has some limitations because of its short half-life. Mesenchymal stromal cells (MSCs) represent an attractive approach for delivery of therapeutic agents to cancer sites owing to their tropism towards tumors, but their immunosuppression capabilities, especially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 43 publications
1
58
0
Order By: Relevance
“…5 The Enterprise Postdoctoral Working Station, Tianjin Chase Sun Pharmaceutical Co., Ltd., Tianjin 301700, China. 6 Precision Medicine Division, Health-Biotech (Tianjin) Stem Cell Research Institute Co., Ltd., Tianjin 301700, China. 7 Jiangxi Research Center of Stem Cell Engineering, Jiangxi Health-Biotech Stem Cell Technology Co., Ltd., Shangrao 334000, China.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 The Enterprise Postdoctoral Working Station, Tianjin Chase Sun Pharmaceutical Co., Ltd., Tianjin 301700, China. 6 Precision Medicine Division, Health-Biotech (Tianjin) Stem Cell Research Institute Co., Ltd., Tianjin 301700, China. 7 Jiangxi Research Center of Stem Cell Engineering, Jiangxi Health-Biotech Stem Cell Technology Co., Ltd., Shangrao 334000, China.…”
Section: Resultsmentioning
confidence: 99%
“…Conclusively, the therapeutics of hESC-MSCs revealed beneficial effects on structural and functional recovery of ischemic muscles in the hind limb ischemia model. Previously, we and other investigators have demonstrated the unique properties of adult tissue-derived MSCs in fundamental research and clinical application [6,8,12,13,19]. However, those cell sources have a number of limitations as well, such as limited long-term in vitro proliferative capacity, donor-specific variability in quality, onset of replicative senescence, and decreased therapeutic potency after continuous in vitro passages [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, TandAb can induce the specific lysis of CD19 + cell lines in the presence of T cells, and an IDO inhibitor could enhance the cytotoxicity of T cells triggered by MSC-TandAb. 419 Clinical studies of IDO inhibitors in lymphomas are still lacking. V-domain immunoglobulin suppressor of T-cell activation (VISTA) is another checkpoint molecule that has a strong inhibitory influence on T cells.…”
Section: Tumor Microenvironment and Checkpoint-related Targeted Therapymentioning
confidence: 99%
“…no. 06366236001; Roche Molecular Diagnostics, Pleasanton, CA, USA) to produce the lentivirus (17). HT29 cells were transduced with the lentivirus for 48 h and selected with 30 µg/ml puromycin (cat.…”
Section: Establishment Of a Cell Line Stably Expressing The Membrane-mentioning
confidence: 99%